2015
DOI: 10.3402/qhw.v10.27749
|View full text |Cite
|
Sign up to set email alerts
|

The social well-being of nurses shows a thirst for a holistic support: A qualitative study

Abstract: IntroductionSocial well-being is one of the important aspects of health. In fact, this is a reflection of experience in a social environment, indicating how social challenges are determined. In other words, social well-being is an explanation of people's perception and experience of being in a good situation, satisfaction with the structure, and social interaction. This qualitative study intended to explore nurses’ experience of social well-being.MethodsQualitative content analysis was used to conduct the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…According to Strauss [35] and Wilkinson [36], the introduction develops critical thinking, clinical assessment and prioritization, crucial skills to enable adaptation, reflection and feedback in a new professional role with a high workload, and new routines and skills. To facilitate this transition, support is needed within a healthy work environment [37][38][39][40]. This finding is consistent with Benner's [5] idea that vocational education that is performed by helpful and positive colleagues contributes to decreased demands.…”
Section: Discussionsupporting
confidence: 62%
“…According to Strauss [35] and Wilkinson [36], the introduction develops critical thinking, clinical assessment and prioritization, crucial skills to enable adaptation, reflection and feedback in a new professional role with a high workload, and new routines and skills. To facilitate this transition, support is needed within a healthy work environment [37][38][39][40]. This finding is consistent with Benner's [5] idea that vocational education that is performed by helpful and positive colleagues contributes to decreased demands.…”
Section: Discussionsupporting
confidence: 62%
“…One of the aspects of health is the psychological and social well-being which was later coined by Selligman, (2012) as 'psychosocial' wellbeing. The study by Mozaffari, et al (2015) states that it is one of the most important factors of health since it reflects directly the interpersonal experience of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Empowerment is an energetic side of creating encouraging work environments for nurses. 25,26 The majority of previous studies 27,28 have indicated that the empowerment of employees can increase the effectiveness and satisfaction of employees and reduced job-related strain. However, this could be considered the first study so far done to measure the relationship between nursing workloads and psychological empowerment using SEM for better recognition.…”
Section: Discussionmentioning
confidence: 99%